2016
DOI: 10.1021/jacs.6b03437
|View full text |Cite
|
Sign up to set email alerts
|

A Thiamine-Dependent Enzyme Utilizes an Active Tetrahedral Intermediate in Vitamin K Biosynthesis

Abstract: Enamine is a well-known reactive intermediate mediating essential thiamine-dependent catalysis in central metabolic pathways. However, this intermediate is not found in the thiamine-dependent catalysis of the vitamin K biosynthetic enzyme MenD. Instead, an active tetrahedral post-decarboxylation intermediate is stably formed in the enzyme and was structurally determined at 1.34 Å resolution in crystal. This intermediate takes a unique conformation that allows only one proton between its tetrahedral reaction ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 38 publications
4
30
0
1
Order By: Relevance
“…As reported previously, the distinct tetrahedral Breslow intermediate in MenD catalysis shows a sharp positive band at λ =302 nm and a broad negative band from λ =305 to 365 nm with double minima at λ =320 and 334 nm by circular dichroism (CD) spectroscopy; this is different from a broad positive band in the ranges of λ =290 to 295 and λ >300 nm that are characteristic of the enamine intermediate in transketolase . These characteristic CD bands are due to the charge‐transfer excitation between the pyrimidine ring and the thiazolium ring of the cofactor, and both were used in our pre‐steady‐state kinetic analysis of the various intermediates in MenD catalysis.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…As reported previously, the distinct tetrahedral Breslow intermediate in MenD catalysis shows a sharp positive band at λ =302 nm and a broad negative band from λ =305 to 365 nm with double minima at λ =320 and 334 nm by circular dichroism (CD) spectroscopy; this is different from a broad positive band in the ranges of λ =290 to 295 and λ >300 nm that are characteristic of the enamine intermediate in transketolase . These characteristic CD bands are due to the charge‐transfer excitation between the pyrimidine ring and the thiazolium ring of the cofactor, and both were used in our pre‐steady‐state kinetic analysis of the various intermediates in MenD catalysis.…”
Section: Resultsmentioning
confidence: 54%
“…This requires that the intermediate is stable enough to withstand exposure to an aqueous environment without being damaged in wait of the incoming electrophilic substrate. Our previous tests demonstrated that this intermediate had the required stability to maintain its characteristic CD spectrum intact for up to minutes without any significant loss in its activity . This high stability strongly supports that the reactive intermediate predominantly takes the neutral tautomeric form with a protonated C 2α center in its equilibrium with the much more unstable carbanion tautomer (Scheme ).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations